Eicosanoid-Activated PPARα Inhibits NFκB-Dependent Bacterial Clearance During Post-Influenza Superinfection - Lucarelli, Ronald; Gorrochotegui-Escalante, Norma; Taddeo, Jessica; Buttaro, Bettina; Beld, Joris; Tam, Vincent (Frontiers in Cellular and Infection Microbiology, 2022)
Secondary bacterial infection (superinfection) post influenza is a serious clinical complication often leading to pneumonia and death. Eicosanoids are bioactive lipid mediators that play critical roles in the induction and resolution of inflammation. CYP450 lipid metabolites are anti-inflammatory lipid mediators that are produced at an excessive level during superinfection potentiating the vulnerability to secondary bacterial infection. Using Nanostring nCounter technology, we have defined the targeted transcriptional response where CYP450 metabolites dampen the Toll-like receptor signaling in macrophages. CYP450 metabolites are endogenous ligands for the nuclear receptor and transcription factor, PPARα. Activation of PPARα hinders NFκBp65 activities by altering its phosphorylation and nuclear translocation during TLR stimulation. Additionally, activation of PPARα hindered anti-bacterial activities and enhanced macrophage polarization to an anti-inflammatory subtype (M2b). Lastly, Ppara–/– mice, which are partially protected in superinfection compared to C57BL/6 mice, have increased lipidomic responses and decreased M2-like macrophages during superinfection.